Prophetic Communication in Historical and Axiological Review - Rahman, Taufik; Indriati, Anisah; Ridwan, Muhammad K. (Fakultas Dakwah UIN Saizu Purwokerto, 2024)
Prophetic communication needs to be reviewed from a historical and axiological perspective. Understanding from a historical point of view means trying to see the Prophet Muhammad as the perpetrator of the history of prophetic communication, reviewing from an axiological point of view to see how far the benefits of this prophetic communication are to human life both personally and communally. Seeing the integration of ethical and aesthetic values that must exist in prophetic communication is the next important part of unraveling prophetic communication from an axiological perspective. The research method used in this research is qualitative with a literature study, analyzing literary references and providing a critical review of prophetic communication in the historical and axiological review of these references. Suppose research on prophetic communication tends to be in the form of implementation. In that case, this research reviews prophetic communication from a historical perspective, which is the initial foundation of prophetic communication, and axiologically to see its application in individual and social aspects more deeply. The ultimate goal resulting from the implementation of prophetic communication is, of course, as we have seen to this day, namely, a change in civilization, specifically the transition from the Jahiliyah era or before the presence of the Prophet SAW to modern life today. The results of this study indicate that prophetic communication is closely related historically and axiologically.